Potensi Lilin Lebah Hutan The Potential Bees Waxs From Wild Bee - Muhammad Junus; Sri Minarti; nur Cholis (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
This research was carried out to examine the ability of forest resources in producing total (amount) nest, hive comb lowering and beeswax of giant honey bee. The method used in this research was survey method. This research was conducted in July 2015 in Sialang Honey Community Cooperative (KOPMAS) located in Sungai Pagar village, Riau province. The result indicated that a). The research location was suitable for giant honey bee (Apis dorsata) development, b). The number of hive combs lowering from 15 trees was 411 combs with 67 times lowering, c). The average of hive comb weight in every lowering was around 40.6 kg. d). Beeswax production at every harvest time was 273.6 kg. The conclusions from this research were: 1). The number of giant honey bee hive combs from various trees and the weight of hive combs were not the same. 2). The amount of beeswax was equivalent to the production of bee hive comb. It is suggested that: 1). The utilization of giant honey bees wax should be designed so it can be used as a commodity to increase people’s incomes. 2). Certain policies are needed to develop giant honey bee activity around forest areas in order to produce more hive comb and beeswax.